DNA barcoding de mamíferos atropelados da amazônia ocidental: um estudo em cutia, cutiara e paca - Aquino, Letícia Maria de (Universidade Federal de São Carlos, 2023)
DNA barcoding is a relatively recent method that allows for the molecular identification of a species from a molecular marker, based on the premise that each species has a unique sequence, which is a barcode sequence. For this, it is necessary to generate sequences from voucher individuals of each species, that is, sequences obtained from an individual that represents the species. The technique can be useful in cases where the morphological identification may not be enough to determine the taxonomy of the species, such as roadkill, where the loss of morphological characters occurs. Thus, the main objective of this study was to verify the use of DNA barcoding methodology in the identification of road-killed mammals on one highway in the Amazon, with emphasis on the Brazilian agouti (Dasyprocta leporina), red acouchi (Myoprocta acouchy) and lowland paca (Cuniculus paca). A total of 21 muscle tissue samples were collected from campaigns promoted by the Reconecta Project in the region of the BR-174 highway, which is located between the city of Presidente Figueiredo-AM and the border of the Roraima state, comprising part of the indigenous territory Waimiri Atroari. After extraction, samples were amplified by PCR using two protocols, which differ mainly in MgCl2 concentrations, primers (COI and 16SrRNA), and annealing temperature. PCR products were purified using polyethylene glycol and sent for Sanger sequencing. The obtained sequences were compared with reference sequences available in public databases. For the analyzed samples, despite several attempts to standardize amplification protocols for the COI gene based on the primers used, the success rate was very low, with only two successful amplified samples. The 16SrRNA gene proved to be an informative region to be used as a barcode for the studied species, obtaining 16 high quality sequences, four of which were identified as C. paca by BLAST tool. Despite the lack of 16SrRNA gene reference sequences for the studied species, phylogenetic analyses show three distinct groups that reflect the three studied species. Considering that there are knowledge gaps regarding the use of primers for the DNA barcoding technique in mammalian group, developing specific primers for taxonomic groups can be useful to increase the success in molecular species identification, especially in case of COI gene. The sequences generated here will be useful to contribute to reference sequence databases for species identification and conservation works carried out by the Reconecta Project.
DNA barcoding of roadkill mammals from the western amazon: a study in brazilian agouti, red acouchi and lowland paca
Keywords: COI; Marcadores moleculares; Atropelamentos; Rodentia; 16SrRNA; Roadkills; Molecular makers; CIENCIAS BIOLOGICAS::GENETICA